Endocervical adenocarcinomas. Cytological, histological, and molecular diagnostics - O. G. Grigoruk; T. A. Moskvina; D. A. Tsoy; A. S. Stepanova; L. M. Bazulina; E. S. Sigitova; T. V. Ponomareva; V. K. Ilinskiy; Yu. A. Bryleva; O. V. Samuylenkova; S. Yu. Bakharev; E. E. Pupkova; et al. (ABV-press, 2022)
This study was undertaken to analyze the effectiveness of cytological diagnostics of endocervical adenocarcinomas. We compared conventional liquid-based cytology, histology, immunohistochemistry, and molecular testing. A total of 25 endocervical adenocarcinomas, including endocervical adenocarcinomas in situ, were diagnosed using cytological methods over a year. Liquid-based cytology ensured better detection of glandular differentiation signs than conventional cytology. After molecular testing for human papillomavirus (HPV), we performed retrospective analysis of cytological characteristics of all endocervical adenocarcinomas (n = 15).We identified specific cellular characteristics of HPV-associated typical and mucinous adenocarcinomas. We also observed 1 case of non-HPV-related clear-cell and 1 case of non-HPV-related mesonephral adenocarcinoma.Our findings suggest that endocervical adenocarcinomas are a heterogeneous group of tumors. Endocervical adenocarcinomas accounted for 10.7 % of all primary cervical carcinomas (n = 214). Eighty percent of all endocervical adenocarcinomas were HPV-related, whereas the remaining 20 % were HPV-negative. We found no cytological differences between invasive endocervical adenocarcinomas and adenocarcinomas in situ.Mutations detected in some of the patients are an important diagnostic criterion that specifies whether the tumor is rare.